2014
DOI: 10.1002/ejhf.103
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction in African patients with acute heart failure

Abstract: Aims In Western countries with typically elderly ischaemic acute heart failure patients, predictors and clinical outcome of renal dysfunction and worsening renal function are well described. However, the prevalence, predictors and clinical outcome of renal dysfunction in younger, mainly hypertensive acute heart failure patients from Africa, have not been described. Methods and results From 1006 patients enrolled in the sub‐Saharan Africa Survey of Heart Failure (THESUS‐HF), renal function was determined by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
(96 reference statements)
4
7
0
Order By: Relevance
“…American and European studies show that treatment recommendations for heart failure are poorly applied [16]. This is particularly true in sub-Saharan Africa, where the implementation of an optimal treatment with titration is particularly difficult because of the lack of patient follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…American and European studies show that treatment recommendations for heart failure are poorly applied [16]. This is particularly true in sub-Saharan Africa, where the implementation of an optimal treatment with titration is particularly difficult because of the lack of patient follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…It is also associated with overweight/ obesity and presence of basal crackles at admission. Presence of renal dysfunction is also independently associated with higher readmission rate over 60 days and all-cause mortality over 180 days [36].…”
Section: Renal Dysfunctionmentioning
confidence: 97%
“…Renal dysfunction has been associated with longer hospital stay and increased hospital mortality in patients with HF. [1,24,27] We found an insignificant increase in mortality and length of hospital stay in patients with renal dysfunction, possibly owing to our sample size. Furthermore, estimation of renal function was done at enrolment, using a single (baseline) serum creatinine value.…”
Section: Researchmentioning
confidence: 63%
“…[23] We found that a third of participants had renal dysfunction, comparable to the findings of the sub-Saharan Africa Survey of Heart Failure (THESUS-HF), in which 30.6% of HF patients had renal dysfunction when admitted to hospital. [24] Similarly, in a metaanalysis of 65 324 HF patients, moderate to severe renal impairment was found in up to 29% of all patients, the prevalence being lower in outpatients than hospitalised patients. [1] In addition to structural renal abnormalities related to hypertension, diabetes or atherosclerosis, renal dysfunction in HF patients may result from renal hypoperfusion caused by haemodynamic, neurohumoral and inflammatory factors.…”
Section: Researchmentioning
confidence: 94%